2007
DOI: 10.1007/s10600-007-0095-0
|View full text |Cite
|
Sign up to set email alerts
|

Chemical enzymatic synthesis of (2′-5′)-oligoadenylates using nuclease from Spicaria violacea mycelial fungus

Abstract: 2′-5′)-Oligoadenylates [ppp5′A(2′p5′A) n , 1] are oligomers of adenylic acid with (2′-5′)-phosphodiester bonds that are synthesized in cells of mammals from 5′-ATP in the presence of interferon and/or double-helix RNA. They are activators of latent endonuclease L, which hydrolyzes mRNA of viruses and is in several instances responsible for the antiviral effect of interferon [1][2][3]. Furthermore, (2′-5′)-oligoadenylates affect cell growth, differentiation, and proliferation and apoptosis [4,5], are active tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Thus, nuclease from FCM of S. violacea performed selective hydrolysis of (3′-5′)-phosphodiester bonds in mixed (2′-5′)-(3′-5′)-oligomers 8 that contain nucleoside units of 6-N-benzyladenosine analogous to that which was observed for compounds based on adenosine [11]. The lack of reaction products with terminal 2′,3′-cyclophosphates indicates that treatment of oligomers 8 with the enzyme complex from FCM of S. violacea also caused hydrolysis of terminal 2′,3′-cyclophosphates in the oligomers.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, nuclease from FCM of S. violacea performed selective hydrolysis of (3′-5′)-phosphodiester bonds in mixed (2′-5′)-(3′-5′)-oligomers 8 that contain nucleoside units of 6-N-benzyladenosine analogous to that which was observed for compounds based on adenosine [11]. The lack of reaction products with terminal 2′,3′-cyclophosphates indicates that treatment of oligomers 8 with the enzyme complex from FCM of S. violacea also caused hydrolysis of terminal 2′,3′-cyclophosphates in the oligomers.…”
mentioning
confidence: 97%
“…We have previously shown that short dephosphorylated (2′-5′)-oligoadenylates (2) can be prepared by enzymatic hydrolysis of long-chain oligonucleotides containing mixed (2′-5′)-(3′-5′)-internucleotide bonds by using (3′-5′)-specific nuclease and phosphatase in the filtrate of culture medium (FCM) of the mycelial fungus Spicaria violacea [11]. The goal of the present work was to develop a chemico-enzymatic method for synthesizing (2′-5′)-oligonucleotides containing 6-N-benzyladenosine (3) moieties as the nucleoside units.…”
mentioning
confidence: 99%